The Magnificat: Cento, Psalm or Imitatio? - Simons, Robert (Tyndale bulletin, 2009)
Scholars have long noted the prominence of LXX words and themes in the Magnificat (Luke 1.46-55). Various attempts have been made to explain this prominence. Some have suggested that the Magnificat is a sort of cento, others that it is modelled upon the OT Psalms. This study will propose that it is an example of what was known in the Graeco-Roman rhetorical tradition as speech in character (προσωποποιΐα) employing the technique of imitatio, and will show that many details in the text of the hymn seem to support this hypothesis.